Kapitał obrotowy netto a sprawność gospodarowania przedsiębiorstw rolniczych - Wasilewski, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents relations between net working capital value in agricultural enterprises and their management effectiveness. The effectiveness of receivables collection in the enterprises was satisfactory. Time of liabilities' regulation was longer than the receivables collection. In enterprises of the highest level of net working capital, stable policy was implemented, by contrast to enterprises of the lowest net working capital level. Inventory management in the enterprises should be evaluated as beneficial. An explicit correlation between longer time of inventory turnover and increase of net working capital value occurred. Negative value of the quick ratio was noticed in the enterprises of the lowest level of net working capital, whereas in the second group of enterprises, the ratio amounted to a high value. There were no essential differences among enterprises of positive value of net working capital concerning economic labour effectiveness. In the enterprises of the lowest net working capital, labour force employment was usually ineffective. Net working capital level is essential regarding evaluation of agricultural enterprises' management effectiveness. Therefore, some actions ought to be taken up in order to optimize relations between working assets and current liabilities. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 588-601